The antidepressant and sedative properties of the ethanolic extracts of Pleurotus squarrosulus on reserpine induced depression anxiety in wistar rats - Akingbesote, Babajide; Salawu, Sule (Nepal Journal of Neuroscience, 2023)
Depression and anxiety are common mental health conditions that can have a significant impact on an individual’s life. Although orthodox treatments for these conditions can be effective, they often accompanied with unfavorable side effects. Oyster mushrooms (Pleurotus spp) have been reported to possess numerous health benefits, including antitumor, antioxidant, and anti-inflammatory effects. The present study aimed to investigate the antidepressant and sedative properties of the ethanolic extracts of Pleurotus squarrosulus. The ethanolic extract of the sample was screened for the presence of bioactive compounds, including alkaloids, saponins, flavonoids, terpenoids, and polysaccharides. The results revealed that the ethanolic extract of Pleurotus squarrulosus exhibited significant radical scavenging ability against 2,2-diphenyl-1-picrylhydrazyl (DPPH) radical, 2,2’-azino-bis (3-ethylbenzothiazoline-6-sulphonic acid (ABTS) radical, nitric oxide (NO), and ferric reducing antioxidant power. The neurobehavioral assessment of rats induced with reserpine showed that Pleurotus squarrulosus extract reduced the immobility time in the tail suspension test (TST) and forced swim test (FST) (p<0.0001), which are behavioral models of depression. Treatment of the Reserpine-induced rats with Pleurotus squarrulosus extract also improved the levels of neurotransmitters acetylcholinesterase, thereby combating the neurotransmitter depletion and oxidative stress induced by their depressive state. The group induced with depression upon reserpine administration resulted in elevated levels of MDA showing high level of peroxidation. The Pleurotus squarrosulus extract as well as the standard antidepressant administered, fluoxetine ameliorated this effect. The groups treated with the Pleurotus squarrosulus extract in the study, was found to increase the activity of antioxidant enzymes, such superoxide dismutase and glutathione peroxidase. This suggests that the extract may have potential as a therapeutic agent for neurodegenerative diseases that involve oxidative stress.